Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1996
DOI: 10.1128/jvi.70.2.960-965.1996
|View full text |Cite
|
Sign up to set email alerts
|

Immunization with viruslike particles induces long-term protection of rabbits against challenge with cottontail rabbit papillomavirus

Abstract: Rabbits were immunized with recombinant baculovirus-produced virus-like particles (VLPs) of cottontail rabbit papillomavirus (CRPV) to determine whether these antigens could induce long-term protection against experimental challenge with CRPV. Infectious CRPV and human papillomavirus type 11 L1 VLPs were used as positive and negative control immunogens, respectively. Three groups of immunized animals were challenged with 10-fold serial dilutions of infectious CRPV at 2 weeks, 6 months, and 12 months after immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(49 citation statements)
references
References 29 publications
0
48
0
1
Order By: Relevance
“…Indeed, papillomavirus-and rotavirus-like particles are potent in generating neutralizing antibodies in vivo. [32][33][34] The function of these anti-E1/E2 antibodies induced by HCV-LP in viral neutralization cannot be tested easily due to the lack of a suitable tissue culture system and a small animal model. Further studies would have to be conducted in a chimpanzee model to test the protective efficacy of HCV-LP.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, papillomavirus-and rotavirus-like particles are potent in generating neutralizing antibodies in vivo. [32][33][34] The function of these anti-E1/E2 antibodies induced by HCV-LP in viral neutralization cannot be tested easily due to the lack of a suitable tissue culture system and a small animal model. Further studies would have to be conducted in a chimpanzee model to test the protective efficacy of HCV-LP.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed many studies have shown that papillomavirus-and rotavirus-like particles are potent in generating neutralizing antibodies in vivo. [10][11][12] Our earlier study has shown that the induced anti-envelope antibodies recognize E2 proteins from different genotypes and were broadly directed against various regions of the E2 protein. 17 However, whether HCV-like particles induce neutralizing antibodies against HCV virions from different genotypes cannot be tested in vitro because there is no reliable tissue culture system available for measuring neutralizing antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Papillomavirus-and rotavirus-like particles synthesized in insect cells have been shown to generate protective immunity. [10][11][12] These studies showed that virus-like particles can induce not only high-titer neutralizing antibodies but also strong cytotoxic T lymphocyte (CTL) responses in immunized animals. [13][14][15] Our laboratory has recently reported the synthesis of hepatitis C virus-like particles in insect cells using a recombinant baculovirus that contains the complementary DNA of the HCV structural proteins (core, E1 an E2).…”
mentioning
confidence: 99%
“…76 They are noninfectious and considered as safe (noninfectious) tools for several purposes such as diagnostic assays, cell interaction studies, and vaccines. [77][78][79][80][81][82][83][84] VLPs are generally more immunogenic than subunit or recombinant immunogens based on single, monomeric proteins. 85 Because of their ordered and highly repetitive structure, they are able to stimulate both the humoral and cellular pathways of the immune system.…”
Section: Virus-like Particle (Vlp) -The Technologymentioning
confidence: 99%